Evaluation of photoelectrocatalytic activity of different BiVO4 films made by electrodeposition inthe degradation of multipollutants - Vieira, Vitória; Sales, Gabriel; da Costa, Antonio; Lima, Rayza; Sales, Ana; da Silva, Rejane; Reis, Roberta; Marques, Gleison; Sales, Lucia; Luz, Geraldo (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Currently, the exacerbated waste water from industrial wastewater causes water matrices to deteriorate gradually. In view of this, the degradation of pollutants using advanced oxidative processes (AOPs) attracted more attention than conventional methods because they are stable, safe and reusable. In this sense, the present work consisted of the production of FTO|BiVO4 films by electrodeposition, where it was evaluated the stability and efficiency of the solution of VO(acac)2 over the course of the days, influence on structural properties, morphological, photoelectrochemical and photoelectrocatalytic activity in the degradation of multipollutants in water (CIP, MTZ and RhB). XRD analysis confirmed the monoclinic crystal structure, of scheelite type, for the films. AFM analyses show the linear reduction of roughness values for samples synthesized with 1, 7, 15 and 30 days with 23.4; 8.6; 7.5 and 3.7 nm, respectively. SEM images show that the films have spherical morphology with small particles. The BiVO4 D1 film exhibited a photocurrent density of approximately 550 μA cm-2. Despite the variations observed in the electrochemical analysis, photoelectrocatalytic tests presented satisfactory results for the films produced, with the BiVO4 D15 film with interesting results for the simultaneous degradation of pollutants, with percentages of 7,00% for CIP, 8.30% MTZ and 33.4% RhB, significantly exceeding the photolysis test.